UJI KINERJA MESIN COMBINE HARVESTER â€œMAXXI CORN TIPE-G AUTOMATICâ€ UNTUK PEMANENAN PADI SAWAH DI DESA TABABO KECAMATAN BELANG KABUPATEN MINAHASA TENGGARA - Stasya P. Rorong; Daniel P.M Ludong; Lady C.CH.E Lengkey (COCOS, 2022)
AbstractCombine harvester Maxxi Corn Type-G Automatic, is a combination of three different operations, arice harvesting machine that can cut the standing grain, thresh and clean the grain while walking in the field,thereby shortening the harvesting time. However, until now there has been no study on the performance ofharvesting capacity, harvesting efficiency and threshing of the Combine Harvester Maxxi Corn Type-GAutomatic in Tababo Village. The purpose of this study was to test the performance of the Combine HarvesterMaxxi Corn Type-G Automatic which is used to harvest rice in Tababo Village which includes, harvestingfield capacity, field efficiency, and threshing capacity. The research method used experimental methods indata collection then all the data obtained were made in the form of tables and graphs and then processeddescriptively. This research uses a Combine Harvester Maxxi Corn Machine Type-G Automatic and a lengthmeasuring device (50 m tape meter), a time measuring device (stopwatch), a scale, a tachometer, a grainmoisture meter, as well as plastic sacks and rice paddies ready to harvest the Adirasa Six Empat variety. witha harvest age of 75 to 80 days and a spacing of 25 x 25 cm on a land size of 15 x 15 m.The performance of theMaxxi Corn Type-G Automatic Combine Harvester in the field produces a theoretical field capacity of 0.3654ha/hour, an effective field capacity of 0.1844 ha/hour and a harvesting field efficiency of 50.6214% and athreshing capacity of 432.54 kg/hour.Keywords:Performance Test Of Machine Combine Harvester Maxxi Corn Tipe-G Automatic